UPAYA GURU AKIDAH AKHLAK DALAM PEMBENTUKAN SIKAP RELIGIUS PESERTA DIDIK PADA MASA PANDEMI COVID-19 DI MTS HASYIM ASYâ€™ARI BATU - Renda Anggrahini; Ach. Faisol; Atika Zuhrotus Sufyana (VICRATINA, 2022)
This study aims to find out how the form of efforts made by aqidah akhlah teachers in shaping the religious attitudes of students during the covid-19 pandemic at MTS Hasyim Asy'ari Batu. This research is a type of descriptive qualitative research. This study focuses on how the teacher's efforts in shaping religious attitudes of students, for data collection the author uses observation, interview and documentation techniques. From the results of this study, it is found that these efforts are carried out by teachers by directing, reminding, and guiding students to have good character in accordance with the teachings of Islam.Â Keywords: teacher efforts, religious attitudes